Infrared Thermally Enhanced 3-Dimensional Time of Flight Magnetic Resonance Angiography Imaging for the Visualization of the Arteries of the Face. Issue 2 (11th May 2020) - Hendrickx, Benoit; Waked, Karl; Mespreuve, Marc
Abstract: Background: The face is known for its extreme variation in vascular anatomy. Furthermore, the rapidly increasing number of filler treatments leads to an increase in severe filler-associated complications (such as skin necrosis and blindness) due to intra-arterial injection. Visualizing a patient's individual complete facial arterial anatomy in a contrast- and radiation-free way has not been published before. This innovative imaging technique could, therefore, enhance the safety of minimally invasive surgical procedures as it provides a harmless way to map the arteries of the face. Objectives: Evaluate a newly developed imaging technique to visualize the arteries of the face in a noninvasive and radiation-free manner. Methods: The individual arterial facial anatomy of 20 volunteers was studied by an imaging technique, combining infrared (IR) facial warming and 3-dimensional (3D) time of flight (TOF) magnetic resonance angiography (MRA). The source and maximum intensity projection images were assessed by 2 investigators, familiar with the anatomy of the face. Results: The MRA technique visualized most of the main facial arteries, albeit in a variable way. The main facial branches of the external carotid artery (facial, angular, supralabial, and superficial temporal arteries) were illustrated well, whereas the visualization of the internal carotid branches (supratrochlear and supraorbital arteries) and nasal branches (dorsal nasal and lateral nasal arteries) was less consistent. Conclusions: The combination of IR "heat-induced enhancement" and a 3D-TOF MRA sequence may actually be an important step toward the visualization of the variable facial vascular anatomy in a noninvasive, radiation-free, and contrast-free manner.